Kemampuan Guru Menggunakan Penguatan (Reinforcement) dalam Pembelajaran di SMPN Kecamatan Bengkalis Kabupaten Bengkalis - Kurniati Kurniati; Ervina Ervina (Akademika: Jurnal Keagamaan dan Pendidikan, 2020)
Reinforcement is a response to a behavior that can increase the likelihood of the behavior recurring. Reinforcement can be done verbally and nonverbally, with principles, enthusiasm, meaningful and positive responses. The problems found are; Most teachers have not yet how to provide good and correct reinforcement and also do not know the benefits of reinforcement in learning. This research is descriptive research. Based on the data obtained, it can be concluded that the form of reinforcement given by teachers at SMP Bengkalis as a whole is varied, but in the results of observations teachers use verbal reinforcement more often than nonverbal reinforcement. This can be seen in the proportion obtained as much as 83.33%. In addition, reinforcement also has a good influence on students and learning goals. This can be seen from the positive response from students and the increased enthusiasm of students in learning and also seen from the percentage obtained as much as 61.11%. The reinforcement given at SMP Bengkalis has varied and is going well.